(untitled) (Tanzania Journal for Population studies and Development, 2015)
Smallholder farming still dominates most agricultural systems in Tanzania. In Njombe and Mvomero districts, it was found out that smallholder farmers face many constraints. The main constraints identified are insufficient skills on dairy cattle husbandry such as proper feeding and animal diseases. This article shows that although there are many constraints in smallholder farming, there are also many opportunities like the availability of land for intensification of agriculture and increased manure production which could be used to improve both soil fertility and increase crop production; and the production of biogas which would reduce the dependence on fuel wood. The article concludes that the key for the advancement of smallholder farming in Njombe and Mvomero districts is increased skills on how to take advantage of crop livestock integrated production.